Seal mothers expend more on offspring under favourable conditions and less when resources are limited - McMahon, CR; Harcourt, RG; Burton, HR; Daniel, O; Hindell, MA (Journal of Animal Ecology, 2017)
Summary In mammals, maternal expenditure on offspring is a complex mix of several factors including the species mating system, offspring sex and the condition and age of the mother. While theory suggests that in polygynous species mothers should wean larger male offspring than females when resources and maternal conditions allow, the evidence for this remains equivocal. Southern elephant seals are highly dimorphic, polygynous capital breeders existing in an environment with highly variable resources and should therefore provide clear evidence to support the theoretical expectations of differential maternal expenditure in male and female pups. We quantified maternal size (mass and length) and pup size at birth and weaning for 342 elephant seal mothers at Macquarie Island. The study was conducted over 11years of contrasting sea-ice and Southern Annular Mode values, both indices of maternal prey resources. Overall, large females weaned male pups that weighed 17kg (155%) more than female pups. Maternal condition varied by as much as 59kg among years, and was positively related to Southern Annular Mode, and negatively to maximum sea-ice extent. Smaller mothers weaned relatively larger male pups under favourable conditions, this effect was less apparent for larger mothers. We developed a simple model linking environmental variation to maternal masses post-partum, followed by maternal masses post-partum to weaning masses and then weaning masses to pup survival and demonstrated that environmental conditions affected predicted survival so that the pups of small mothers had an estimated 7% increase in first year survival in good vs. bad years compared to 1% for female pups of large mothers. Co-occurrence of environmental quality and conservative reproductive tactics suggests that mothers retain substantial plasticity in maternal care, enhancing their lifetime reproductive success by adjusting reproductive expenditure relative to both prevailing environmental conditions and their own capabilities.